Individual recognition through olfactory–auditory matching in lemurs - Kulahci, Ipek G. (The Royal Society, 2014)
Individual recognition can be facilitated by creating representations of familiar individuals, whereby information from signals in multiple sensory modalities become linked. Many vertebrate species use auditory–visual matching to recognize familiar conspecifics and heterospecifics, but we currently do not know whether representations of familiar individuals incorporate information from other modalities. Ring-tailed lemurs (Lemur catta) are highly visual, but also communicate via scents and vocalizations. To investigate the role of olfactory signals in multisensory recognition, we tested whether lemurs can recognize familiar individuals through matching scents and vocalizations. We presented lemurs with female scents that were paired with the contact call either of the female whose scent was presented or of another familiar female from the same social group. When the scent and the vocalization came from the same individual versus from different individuals, females showed greater interest in the scents, and males showed greater interest in both the scents and the vocalizations, suggesting that lemurs can recognize familiar females via olfactory–auditory matching. Because identity signals in lemur scents and vocalizations are produced by different effectors and often encountered at different times (uncoupled in space and time), this matching suggests lemurs form multisensory representations through a newly recognized sensory integration underlying individual recognition.